Monitoring the impact of COVID-19 pandemic on mental health: a public health challenge? Reflection on Italian data - Gualano, Maria Rosaria (Soc Psychiatry Psychiatr Epidemiol, 2020)
A recent Italian report on medicines use during COVID-19 epidemic outlined a non-significant increase in outpatient pharmaceutical antidepressant consumption in March and a significant increase in anxiolytic consumption. Along with this, an analysis of psychiatric hospitalizations in Lombardy revealed a reduction in voluntary admissions in the 40 days after the beginning of COVID-19 epidemic in Italy. Nevertheless, several studies reported a greater prevalence of depressive and anxiety symptoms in the Italian general population during the lockdown compared to before the pandemic. Furthermore, the request for psychological support by the Italian population appeared to be high during lockdown. Indeed, the Italian Ministry of Health declared that more than 50,000 calls to the telephone number for psychological support activated by the Ministry of Health and the Civil Protection because of the pandemic, with peaks during the lockdown. In addition, looking at Google Trends, the greatest searching activity for “psychological support” in recent years was detected the week of the 26th April 2020, followed by the week of the 22nd March 2020. We think that stronger indicators of mental health status and psychological well-being should be found to understand the long-term effects of the pandemic. The necessity of research for population-level and universal strategies is urgent, through repurposing, developing, and testing interventions to create evidence-based action plans for the entire population. Lastly, it is also essential to keep offering a psychological support suitable for all as done in past months to help individuals who have fewer opportunities to access care.